Effect of new water-soluble phenolic antioxidants on the activity of Nrf2-driven enzymes, glutathione system, and Nrf2 translocation into the nucleus - E. B. Menshchikova; N. K. Zenkov; P. M. Kozhin; A. V. Chechushkov; V. S. Pavlov; L. P. Romakh; M. V. Khrapova; A. E. Serykh; O. B. Gritsyk; N. V. Kandalintseva (Сибирский научный медицинский журнал, 2020)
Understanding the role of reactive oxygen and nitrogen species in eustress (redox balance) and distress (oxidative stress) development poses new challenges for biomedical scientists and pharmacologists in the search for compounds that can not only have a direct antioxidant (antiradical) effect, but also affect redox-sensitive signaling pathways, primarily Keap1/Nrf2/ARE system. Aim of the study was to investigate the influence of novel water-soluble structurally related monophenols on key elements of Keap1/Nrf2/ARE system induction (activity of Nrf2-driven enzymes, the state of the glutathione system, and intracellular redistribution of transcription factor Nrf2).Material and methods. Five original hydrophilic structurally related monophenols, differing in the number of tert-butyl ortho-substituents, the length of the para-alkyl substituent, and the presence of a divalent sulfur or selenium atom in it were investigated (phenoxane, the potassium salt of phenosan acid, was used as a reference compound). Cell lines U937 and J774 were cultured for 24 h in the presence of tested compounds, and comparative analysis was performed of its ability to induce the synthesis of Nrf2-driven enzymes of phase II xenobiotic detoxification pathway and antioxidant enzymes (NAD(P)H: quinone oxidoreductase 1 (NQO1), glutathione S-transferases (GST), glutathione peroxidases, glutathione reductase (biochemical spectrophotometric methods were used to study their activity), as well as to influence the state of glutathione system (spectrophotometry) and translocation of transcription factor Nrf2 into the nucleus (immunofluorescent staining, confocal microscopy) (key events of Keap1/Nrf2/ARE signaling system activation).Results and discussion. Monophenol TS-13 have found to be the most effective inducer of tested enzymes in U937 cells among the structural analogs, while the structure of the para-alkyl substituent and the degree of OH group hindrance are important for the implementation of this effect; TS-13 also effectively enhanced Nrf2 import into J774 cell nucleus. The NQO1- and GST-inducing abilities of structurally related monophenols are closely interrelated, which indicates the possibility of coordinated induction of these enzymes and the presence of a common regulatory system that ensures their activation in response to cell treatment with phenolic antioxidants.